Kewenangan Satuan Petugas Illegal Fishing Dalam Penegakan Hukum Kelautan Dan Perikanan Di Indonesia - Pery Rahendra Sucipta; Putri Arfina (Journal of Judicial Review, 2016)
The purpose of this study was to analyze marine and fisheries law enforcement by agencies who are the members of the Unit Officers on Illegal Fishing who have had their respective authorities by the legislation. Analysis of these authorities in terms of legislation of the respective state agencies involved in marine and fisheries law enforcement. Formation of Illegal Fishing Unit is considered to pose authority overlapping with relevant state institutions, thus causing the ineffectiveness of the law enforcement of marine and fisheries.The methodology that used in this study is a normative legal research. The used data is secondary data which is obtained from the literature (library research). After all data are collected, then can be processed and analyzed, the analysis use qualitative point by grouping the studied aspects data. Furthermore, the conclusions are drawn related to this study, then elaborated descriptively.Based on this study, the results are reviewed by researchers from the two (2) formulation of the problem, first regarding the enforcement of maritime affairs and fisheries associated with positive law and second the authority of the Unit Officers on Illegal Fishing, as ruled in Presidential Decree No. 115/2015 about Unit Officers on Eradication of Fishing Illegally.